Lucy Mission Search Plans for Activity around Its Jovian Trojan Flyby Targets - S. Alan Stern; Carly Howett; Neil Dello Russo; Harold A. Weaver; James F. Bell III; Dennis Reuter; Amy Simon; Hannah Kaplan; Keith Noll; John Spencer; Simone Marchi; Hal Levison (The Planetary Science Journal, 2025)
Activity in small bodies, defined here as the episodic or continuous release of material, was long thought to be exclusively a behavior of comets, but it has since been discovered in some centaurs, main-belt asteroids, and near-Earth asteroids. To date, however, no activity has been discovered on Jovian trojan asteroids, the target of NASA’s Lucy Discovery Program mission. Although Lucy was originally conceived without studies of or searches for trojan activity, it was realized in 2016–2017 that the spacecraft and scientific payload aboard Lucy could provide unique and meaningful constraints or detections on activity in these trojans. Here we describe how the Lucy mission will search for such activity using (i) its terminal tracking navigation camera to search for wide-field coma scattered light, (ii) its Lucy Long Range Reconnaissance Imager narrow-angle camera to also search for scattered light from any coma or jets, and (iii) its Multispectral Visible Imaging Camera imager to search for CN emission (a common activity tracer species in comets). Sensitivity estimates for each of those measurements are discussed below.